Marine cyanobacteria of Costa Rica: published records - Brenes-Guillén, Laura; Fernández-García, Cindy; Cortés, Jorge (Revista de Biología Tropical, 2025)
Introduction: Cyanobacteria, also known as blue-green algae, are photosynthetic bacteria that play a crucial role in the marine environment, including food and oxygen production, nitrogen fixation, yield antibiotics and other bioproducts which might be used by other members of the community. Cyanobacteria remain understudied, particularly in the marine environments of Central America. While research on cyanobacteria has been conducted in Costa Rica, most studies have focused on freshwater environments, leaving a significant gap in understanding their diversity in the region. Objective: This study compiles the diversity of marine cyanobacteria in Costa Rica through a review of scientific publications and herbarium collections. Methods: a review of the scientific literature and cyanobacterial specimens from the Pacific and Caribbean from 1936 to the present was conducted. In November 2023, the Dr Luis A. Fournier Origgi Herbarium at the University of Costa Rica was visited to examine the available specimens. Results: We found 50 records of cyanobacteria in the references and herbarium collections, of which 10 belonged to Sections I and II, 26 to Section III, nine to Section IV and five to the unclassified category. Genomic data from two studies were found in public databases. Conclusions: The diversity of marine cyanobacteria in Costa Rica represents a valuable resource for ecological and evolutionary studies. This work provides a baseline for future research and highlights the importance of continuing to explore and document the biodiversity of these bacteria.